Mechanical Thrombectomy for Cerebral Venous Thrombosis in a Young Female on Oral Contraceptive - Adnan, Ahmad Faiz; Ezamin; Tharek, Anas; Bin Kamis, Mohd Fandi Al Khafiz; Bin Muda, Ahmad Sobri; Md Noh, Mohamad Syafeeq Faeez (The Interventionalist Journal, 2025)
This case report details the management of a 33-year-old female patient presenting with cerebral venous thrombosis (CVT), a rare but potentially fatal condition, and our experience in performing mechanical thrombectomy as a life-saving intervention. The patient, who was on oral contraceptives, was successfully treated using a combination of aspiration thrombectomy and stent retriever techniques, leading to a significant neurological improvement and full recovery. Our report emphasizes the importance of a multidisciplinary approach and early intervention in the management of complex CVT cases, as well as highlights the role of interventional radiology in achieving successful patient outcomes